Numerical Analysis of Turbulent Flow and Heat Transfer in Internally Finned Tubes - Liu, Zhanwei; Yue, Yanwei; She, Luchao; Fan, Guangming (Frontiers in Energy Research, 2019)
In this study, single-phase heat transfer enhancement in internally finned tubes is investigated numerically. The influence of fin number, helix angle, fin height, fin width, and shape on the flow and heat transfer characteristics is studied. The research results indicate that the resistance coefficient and Nusselt number both increase with the increment of these parameters, among which the helix angle has the largest impact on the heat transfer enhancement. In addition, the shape of fins also has a small effect on the flow and heat transfer, and the heat transfer effect of triangular fins is the best.